Comparison of Growth Performance of Nannochloropsis oculata Biofilm at Different Layers of Substrate Plastic - Rachmawati Rusydi; Muliani Muliani; Angga Dian Pratama Matondang (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
Biofilm based microalga is a structured community of microalgae attaching to substrate with a self-produced matrix of extracellular polymeric substances (EPS). One of microalgae that is potential to be improved as biofilm is Nannochloropsis oculata. Biofilm of Nannochloropsis oculata has some beneficial roles such as bioremediator of polluted waters. This study was aimed to evaluate the growth performance of Nannochloropsis oculata at different layers of substrate plastic as biofilm substrate. The experimental design used was Completely Randomized Design (CRD) with four level treatments and three replications. Several treatments tested were A: Control (without layer), B: 1 Layer of substrate, C: 2 Layers of substrate, D: 3 Layers of substrate. Several procedures were conducted in this study which were preparation of KW21 medium, cultivation of biofilm at different treatments in KW21 medium, and growth measurement. The results of this study showed that different number of substrate layers could affect the specific growth rate of free cells of Nannochloropsis oculata. The highest growth rate was found in treatment B (1 substrate layer) and the lowest one was in treatment D with their values 0.064 µ/day and 0,037 µ/day. The peak population of Nannochloropsis oculata was obtained at day 14 until 15.